Foliar Endophytic Fungi from the Endangered Eastern Mountain Avens (Geum peckii, Rosaceae) in Canada - Sarah J. Adams; Brent M. Robicheau; Diane LaRue; Robin D. Browne; Allison K. Walker (Plants, 2021)
Eastern Mountain Avens (Geum peckii Pursh, Rosaceae) is a globally rare and endangered perennial plant found only at two coastal bogs within Digby County (Nova Scotia, Canada) and at several alpine sites in the White Mountains of New Hampshire (USA). In Canada, the G. peckii population has declined over the past forty years due in part to habitat degradation. We investigated the culturable foliar fungi present in G. peckii leaves at five locations with varying degrees of human impact within this plant species’ Canadian range. Fungal identifications were made using ITS rDNA barcoding of axenic fungal cultures isolated from leaf tissue. Differences in foliar fungal communities among sites were documented, with a predominance of Gnomoniaceae (Class: Sordariomycetes, Phylum: Ascomycota). Habitats with more human impact showed lower endophytic diversities (10–16 species) compared to the pristine habitat (27 species). Intriguingly, several fungi may represent previously unknown taxa. Our work represents a significant step towards understanding G. peckii’s mycobiome and provides relevant data to inform conservation of this rare and endangered plant.